2001
DOI: 10.1007/s002940100205
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient expression of rabbit neutrophil peptide-1 gene in Chlorella ellipsoidea cells

Abstract: A highly efficient system was developed for the expression of foreign genes in Chlorella ellipsoidea cells. The effect of five promoters on the expression efficiency of beta-glucuronidase (GUS) gene was evaluated by transient expression of the UidA gene. Among these promoters, Ubiquitin-omega was found to be the most efficient and was selected to drive the expression of foreign genes in Chlorella cells. A gene encoding the mature rabbit neutrophil peptide-1 (NP-1) was introduced into the cells. Integration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 0 publications
0
53
0
Order By: Relevance
“…has been hindered by the lack of genomics research models. Moreover, although genetic modification of Chlorella vulgaris (Chow and Tung, 1997) and Chlorella ellipsoidea (Chen et al, 2001) were achieved, none of the Chlorella spp. strains shown to be amenable to transformation are of commercial interest (Tran et al, 2013).…”
mentioning
confidence: 99%
“…has been hindered by the lack of genomics research models. Moreover, although genetic modification of Chlorella vulgaris (Chow and Tung, 1997) and Chlorella ellipsoidea (Chen et al, 2001) were achieved, none of the Chlorella spp. strains shown to be amenable to transformation are of commercial interest (Tran et al, 2013).…”
mentioning
confidence: 99%
“…More recently, Geng et al (2003) described both the stable and transient nuclear transformation of D. salina using electroporation and expression of the hepatitis B surface antigen under the control of the maize ubiquitin-promoter, a promoter that has previously been used for the expression of foreign genes in Chlorella ellipsoidea (Chen et al, 2001). While the rate of transient transformation was relatively low, at least 14 positive lines were confirmed by PCR and Southern blot analysis although stable integration of the transgene was not determined.…”
Section: Discussionmentioning
confidence: 96%
“…Results showed that the transformed plants inhibited B. subtilis and P. aeruginosa growth, which was consistent with the results of NP-1 genes introduced into poplar and Chlorella (Zhao et al, 1999;Wang et al, 2001). The NP-1 disease-resistant mechanism was combined with a virus coat protein to lose their biological activity (Chen et al, 2001b). However, only three strains showed better inhibitory effects in six positive transgenic plants, which may be owing to the following: first, the low expression of the NP-1 gene; there is a threshold level of transgene-derived transcripts, and disease-resistant mechanisms cannot be triggered until the threshold level in transgenic plants is reached (Fu et al, 1998); second, the genetic variation of other disease-resistant related genes during the process of transformation; and third, false positives.…”
Section: Discussionmentioning
confidence: 99%